Between Remembrance and Oblivion: Negotiating Civic Identity after the Sacks of Mechelen (1572, 1580) - Boer, David de (The sixteenth century journal, 2020)
In 1572, Mechelen was the first city to be sacked by a Habsburg army during the Dutch Revolt. The Duke of Alba punished its citizens for having opened the gates to rebels. In 1580, the city was sacked again, this time by a Protestant rebel army. Being sacked acutely raised the question of what it meant to be part of a civic community. In both cases, however, political circumstances made it difficult to communicate the memory of the violent takeover. Harking back to the so-called Spanish and English furies ostensibly meant commemorating a rebellious past. This went against the Habsburgs’ policy of oblivion—requiring reconciled cities to move on and forget about their experiences. To better understand how atrocity shaped individual and civic identity, this article examines the strategies that citizens used to make sense of painful memories in an unstable and divided political landscape.